Textural/structural, stability and morphological properties of mesostructured silicas (MCM-41 and MCM-48) prepared using different silica sources - Gaydhankar, T. R.; Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Kumar, R (Catalysis Communications, 2005)
A series of MCM-41 and MCM-48 samples have been synthesized under hydrothermal and static conditions using different silica sources (fumed silica, silica sot and ethyl silicate) and characterized by powder XRD, scanning electron microscopy and N-2 adsorption. The silica source reactivity trend observed was as: ethyl silicate > fumed silica > silica sot. However, the extent of contraction caused by calcination, magnitude of the wall thickness and stability were found to depend not only upon the type of silica source used but also on the type of structure formed. Noticeable morphological differences were observed in case of only MCM-41 when silica sources were varied. © 2005 Elsevier B.V. All rights reserved.